WHAT DO THEY LIKE AND DISLIKE FROM GAME-BASED ENTREPRENEURSHIP LEARNING? A QUALITATIVE STUDY - Muhamad Ahsan; Aun Falestien Faletehan (LPMPP Universitas Negeri Yogyakarta, 2021)
One of the ways to raise an entrepreneurial spirit through learning processes is the use of game simulation. Learning materials delivered using game simulation are expected to improve knowledge, understandings, and insights related to entrepreneurship. This study aimed to examine individual’s understanding of game-based entrepreneurship learning based on the expressions of like and dislike. Data of this study were collected by means of an open-ended questionnaire through a survey conducted for nine years (2011-2019). As many as 441 students participated in the entrepreneurship game called “Start and Improve Your Business (SIYB)” at a university in Indonesia. The collected data were analyzed qualitatively using NVivo 12plus. The results showed that participants liked the game because it could increase their entrepreneurial passions, skills, insights, and mindsets. However, what participants did not like about the game was related to its’ characteristics, the personal issues that it came out with, and the teamwork in the game. This study contributes to the development of a game-based entrepreneurship learning model by identifying participants' interests and discussing the strengths and weaknesses of the game implementation.